Reflections of the Civil War in southern humor - Hall, Wade, 1934-2015 (NewSouth Books, 2015)
As one of the organic forms of literature, humor has always responded to and reflected the needs of the people at a given time, and the Civil War and its aftermath were days of the South's greatest need. Historians have suggested many reasons for the South's fearless stand against "overwhelming numbers and resources," to use General Lee's words. In this short study, author and historian Wade Hall adds one reason to the list: the humor of the Southerner -- as soldier and civilian -- during the war and the bleak days that followed it. The South arose from the ashes of humiliation and defeat smiling -- though sometimes through tears. The Southerner's sense of humor helped him to fight a war he believed honorable and to accept the bitter defeat which ended it. Without the escape valve of humor, many a "rebel" would have succumbed to despair. The Southerner could smile wistfully as he looked back on a proud past and hopefully as he looked forward to an uncertain future. He smiled because he read humorists like Bill Arp, who once wrote somewhat serio-comically that the South was "conquered but not convinced." In this study, Hall has attempted to represent all the types of humor written in the South between the beginning of the Civil War and the beginning of World War I, specifically 1861 and 1914, including war memoirs, novels, plays, short stories, poetry, and songs. After a survey of humor written during the war, Hall discusses the soldier, the Negro, the poor white, and the "folks at home" in wartime, as they are reflected in the postwar humor.